Prenatal exposure to testosterone increases ectoparasite susceptibility in the common lizard (Lacerta vivipara). - Uller, T; Olsson, M (2003)
High levels of testosterone can benefit individual fitness, for example by increasing growth rate or ornament size, which may result in increased reproductive success. However, testosterone induces costs, such as a suppressed immune system, thereby generating trade-offs between growth or mate acquisition, and immunity. In birds and reptiles, females allocate steroids to their eggs, which may be a mechanism whereby females can influence the phenotype of their offspring. To our knowledge, only the benefits of early androgen exposure have been experimentally investigated to date. However, to understand this phenomenon, the costs also need to be evaluated. We manipulated testosterone levels in eggs of the viviparous common lizard and monitored growth, endurance and post-parturient responses to ectoparasites of the offspring. Testosterone-treated individuals had significantly higher growth rates than controls, but suffered a significant decrease in growth rate when exposed to ticks, whereas the corresponding difference for controls was non-significant. There was no difference in observed parasite load or leucocyte count between manipulated and control offspring. Thus, our results suggest that high testosterone levels during embryonic development have detrimental effects on immune function resulting in reduced growth rate, and that this must be taken into consideration when evaluating the potential adaptive value of maternal androgen allocation to eggs.